2016
DOI: 10.1371/journal.pone.0152825
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Plaque Vulnerabilities in Patients with Acute Myocardial Infarction

Abstract: ObjectiveAlthough the plaque characteristics have been recognized in patients with acute myocardial infarction (AMI), the plaque spatial distribution is not well clarified. Using color-mapping intravascular ultrasound (iMAP-IVUS), we examined culprit lesions to clarify plaque morphology, composition and spatial distribution of the sites of potential vulnerability.MethodsSixty-eight culprit lesions in 64 consecutive AMI patients who underwent angiography and IVUS examinations before intervention were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(41 reference statements)
0
2
0
2
Order By: Relevance
“…When the incrassation of IMT reached over 1.5 mm, plaque burden was evidently increased, which accompanied by significant increase of PA, decreased nutrition supply of plaque and secondary ischemia, necrosis and rupture in the plaque, resulting in acute complete occlusion in distal coronary. [ 18 , 19 ] Echo in plaque region by this time was characterized by heterogeneity and low echo. During IMT thickening that caused by a little lipid deposition in the early stage, intima was lacking in smoothness, PA increase was not evident, and plaque echo showing hyperechoic, indicated that steady progressing plaque was mainly formed, and compensatory adjustments could be proceeded in human body to lower the occurrence of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…When the incrassation of IMT reached over 1.5 mm, plaque burden was evidently increased, which accompanied by significant increase of PA, decreased nutrition supply of plaque and secondary ischemia, necrosis and rupture in the plaque, resulting in acute complete occlusion in distal coronary. [ 18 , 19 ] Echo in plaque region by this time was characterized by heterogeneity and low echo. During IMT thickening that caused by a little lipid deposition in the early stage, intima was lacking in smoothness, PA increase was not evident, and plaque echo showing hyperechoic, indicated that steady progressing plaque was mainly formed, and compensatory adjustments could be proceeded in human body to lower the occurrence of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Plaque ruptures occur predominantly in the vicinity of the maximum necrotic core site and tend to be proximal to the maximum plaque burden and minimum lumen area sites. The ruptures occurred at the maximum necrotic core sites in 26% and either proximal (44%) or distal (30%) to it in the remaining 74% suggesting that the longitudinal shoulder of the maximum necrotic core site is the weakest point for plaque rupture [ 31 ]. Few other studies also have shown that the maximum necrotic core site is located proximal to the severe most stenosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antoni et al 16 avaliaram a frequência e distribuição de lesões ateroscleróticas em 1533 indivíduos adultos com diagnóstico de IAMCSST e identificaram que a maior parte das lesões encontradas se situava nas regiões proximal e média das artérias. Zheng et al 17 verificaram uma predominância de 50% das lesões da sua amostra na DA. Em nosso estudo, a artéria com menos lesões foi a TCE, dado que corrobora com o exposto por Wang et al 18 , que encontraram apenas um caso de trombose no TCE nos 208 participantes com IAMCSST.…”
Section: Discussionunclassified
“…Em relação às características da amostra estudada, observa-se semelhança a outros estudos sobre o tema, com destaque para a distribuição das principais comorbidades associadas à DAC, a maior prevalência entre homens e a média etária 16,17 . A elevada proporção de ex-tabagistas e tabagistas com consumo inadequado de FVL na população estudada também é observada por outros estudos.…”
Section: Discussionunclassified